MANGIFERA INDICA (AMRA) AND ITS SEED KERNEL - AN USEFUL DRUG - Ganeriwala, *Baby; Gudaganatti, K. S.; Bolmal, U B (International Journal of Ayurveda and Pharma Research, 2016)
Mangifera indica (Amra), family Anacardiaceae, a large plant found wild or semi- wild nearly throughout India in tropical and sub-tropical hilly forests. Commonly it is cultivated throughout the country for its fruits and is widely used in folk and Ayurvedic system of medicine. Various parts of plant contain mangiferine, amino acid, gallotannin, gallic acid, m-digallic acid, ethylgallate, isoquercetinquercetin and β – sitosterol, fat, calcium, protein and tannic acid. Therapeutic indications of Mangifera indica mentioned in Ayuvedic classical texts are Vaman (vomiting), Atisar (diarrhea), Hridadaha (heart burn), Raktasrava, Bhagnasandhana, Yoni roga etc, whereas from modern point of view it has Antibacterial, Anti-fungal, Antiviral, Antioxidant, Antipyretic and Antiamoebic properties. In this review efforts are made to discuss various aspects of Amra, which will certainly help the researchers to a great extent in their field.